Technological extension program pilot project implemented in the capital goods sector in São Paulo - Brazil : promoting technological innovation - Bueno, Dorotéa (2011)
Technological extension is recognized by the Organisation for Economic Co-operation and Development (2005, OECD) as fundamental for economic development, by promoting and stimulating further technological innovation, especially in small and medium-sized enterprises (SMEs). Despite its importance, particularly with respect to the impact of public or private initiatives that promote technological extension within the SMEs, the technical literature is not abundant on this subject and just a few case studies can be found. Moreover, development of structured extension programs based on the transposition of experiences between countries is very complex, mainly due to the diversity of economic, cultural, political and technological realities. Another important challenge is related to the concept and the structural base of the technological extension. This paper is written using the methodological reference and systematization of information available in the bibliography from the OECD. Based on this reference, the Ministry of Science and Technology of Brazil started four pilot projects to be implemented in São Paulo, Paraná, Santa Catarina and Bahia. These projects had two main objectives of putting in practice the technological extension service and analyzing its impact on firms. This article presents the process of implementation of the pilot in São Paulo. In this project, fifty firms of the capital goods sector were investigated. The results were the following: many firms showed improvement in the management of the production flow, a more consistent planning, a better control of many phases in the activity of the firm and increases in productivity. Based on these results, it can be concluded that the pilot program’s technological extension proved to be relevant to SMEs due to specific management actions focused on the real needs of each firm, combined with the technological support provided and the low financial investment made by firms. Since this is a new and unknown project to most firms, many businessmen manifested doubts and uncertainty concerning the program. In this sense, after the evaluation of the whole process of implementing the pilot project, it was suggested to extend the same project to economic sectors in São Paulo. With this enlargement, it is intended to achieve a better promotion and publicity as well as adopting the concept of the technological extension. The program became effective as a part of the Science, Techonology and Innovation Program promoted by the Brazilian government.